Direct prismatic coefficient variation to hull form surface - Dayeon Jeong; Min-Jae Oh (International Journal of Naval Architecture and Ocean Engineering)
The initial ship design process aims to optimize the hull form to enhance ship efficiency. During this phase, hull form variations are executed based on a reference ship to meet shipowner requirements, such as altering the CP (prismatic coefficient) to adjust the section lines. Once these variations are made, a surface is generated. However, this iterative process can be time-consuming as the surface creation must be done manually each time. Thus, we propose a method to directly apply CP variation onto the hull form surface, setting the variated section line as a constraint. In this study, the proposed method is employed to modify the hull form surface to meet CP requirements. The section lines of the modified surface are then extracted to validate the results. This streamlines in the initial hull form design, reduces the overall design time, and yields high-quality hull form surfaces efficiently.